Ab initio calculations of Stark broadening parameters of C II spectral lines. (November 2022) - Liang, Rihui; Liu, Yanming; Li, Fangyan
Highlights: The Stark broadening parameters of singly ionized carbon were predicted by making use of Griem's semiempirical method. The calculated results are tabulated in the wide range of emission frequency for various electronic temperatures and densities. Atomic Stark broadening parameters are of vital significance for spectroscopic community due to their wide applications. Abstract: Stark broadening is widely used in many research areas, but its applications are limited by the completeness of line width and shift. Based upon the transition line data evaluated by Kramida, we have predicted the Stark broadening parameters of singly ionized carbon by making use of Griem's semiempirical method. The comparison with experimental and theoretical data is conducted and the results presented also. The Stark widths and shifts in this work agree very well with the measured and theoretical results within the margins of the error. The calculated results are tabulated for an electron density of 10 17 cm −3 and temperatures varying about 10000 K to 50000 K. These parameters may have application prospects in optical diagnosis of laboratory plasma, spectral simulation in astrophysics and radiation modeling of high-temperature gases or plasmas.